Lifestyle and environmental risk factors associated with overweight/obesity in white women from the Lejweleputswa District, South Africa - Lyell, Ilze (University of the Free State, 2015)
The aim of this study was to describe the lifestyle and the profile of known environmental risk factors for overweight/obesity that exist among the white women of the Lejweleputswa district in the Free State province of SA.

Die doel van hierdie studie was om die leefstyl- en profiel van bekende omgewingsrisikofaktore vir oormassa/vetsug te bespreek wat voorkom tussen die blanke vroue van die Lejweleputswa distrik in die Vrystaat provinsie van Suid-Afrika.
Dissertation (M.Sc. (Nutrition and Dietetics))--University of the Free State, 2015
Keywords: Overweight; Obesity; Fat accumulation; South African women; Health risk factors